Graph Transformation 7th International Conference, ICGT 2014, Held as Part of STAF 2014, York, UK, July 22-24, 2014, Proceedings - Giese, Holger; König, Barbara (Theoretical Computer Science and General Issues, 2014)
This book constitutes the proceedings of the 7th International Conference on Graph Transformations, ICGT 2014, held in York, UK, in July 2014. The 17 papers and 1 invited paper presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on verification, meta-modelling and model transformations, rewriting and applications in biology, graph languages and graph transformation, and applications.